Violencia de pareja en Bolivia: Previene el trabajo remunerado de las mujeres la violencia en su contra? - Adriana Montenegro (Universidad Católica Boliviana, Instituto de Investigaciones Socio-Económicas (IISEC), 2021)
– There is an apparent consensus, at the level of public policies, about the empowering effect of working outside the home for women, thereby reducing the levels of violence against them. However, the empirical evidence on the female labor-violence relationship is inconsistent. In the face of this inconsistency, this investigation examines the effect of the productive work of married or cohabiting women in Bolivia, on their probability of being a victim of partner violence during 2016, using the data from the Survey of Prevalence and Characteristics of Violence Against Women. Using a bivariate probit model, it was possible to conclude that the work does not have a significant effect on the propensity of a woman to suffer partner violence, once the endogeneity bias has been corrected. On the other hand, other variables do relate significantly to the phenomenon, such as the experience of violence in the home of origin (both the victim and their partner), which increases it considerably, and education or age of women at the time of union, which reduces it.
Keywords: J12; E24; C25; 330; Spousal Violence; Employment Status; Bivariate Probit; Bolivia; Ehe; Gewalt; Erwerbstätigkeit; Frauen; Probit-Modell; Bolivien